Antimicrobial Resistance Profiles of Bacterial Isolates from Clinical Cases in Livestock and Poultry - Dhoral, Jayesh; Solanki, Sudeep; Sharma, Deepak; Singathia, Rajesh; Gaurav, Abhishek (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
This study investigated the antimicrobial resistance profiles of bacterial isolates from clinical cases in ruminants (n=163) and poultry (n=64). In ruminants, Staphylococcus aureus exhibited the highest resistance to penicillin-G (85.45%), tetracycline, and polymyxin-B (80% each). Streptococcus spp. showed the greatest resistance to polymyxin-B (100%) and methicillin (86.67%). E. coli isolates displayed maximum resistance to penicillin-G, cephalothin, methicillin, and vancomycin (100% each), while Salmonella isolates were resistant to methicillin (100%), vancomycin (85.71%), and polymyxin-B (85.71%). All Corynebacterium spp. were fully resistant to nitrofurantoin, and all Pseudomonas isolates were resistant to ampicillin, nitrofurantoin, penicillin-G, methicillin, tetracycline, and vancomycin. In poultry, E. coli exhibited complete resistance to nitrofurantoin, vancomycin, penicillin-G, methicillin, and cephalothin, followed by tetracycline (88%), co-trimazole (88%), polymyxin-B (84%), and ampicillin (80%). Salmonella isolates were resistant to methicillin (100%), vancomycin (80%), polymixin-B (80%), and ampicillin and co-trimoxazole (73.33%). Proteus mirabilis exhibited high resistance to penicillin-G, methicillin, tetracycline, nitrofurantoin, vancomycin, and cephalothin (100% each), followed by co-trimazole (91.67%) and polymyxin-B (88.33%). Klebsiella isolates showed over 90% resistance to penicillin-G, polymyxin-B, vancomycin, methicillin, cephalothin, and ampicillin. Antimicrobials penicillin-G, methicillin, tetracycline, co-trimoxazole, ampicillin, vancomycin, and amoxicillin-clavulanic acid exhibited 100% high resistance in Pseudomonas isolates. The least resistance was observed in all isolates to gentamicin, ciprofloxacin, ofloxacin, chloramphenicol, amoxicillin-clavulanic acid, and azithromycin.